Utter, Don (audio interview #3 of 5) - Utter, Don (1919 - 7/20/1997); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This is the third of five interviews that were conducted at Utter's home in Belmont Shore. The interviewer met him while serving on a LWV's committee to prepare a pamphlet about local history. Utter subsequently became a student of the interviewer as part of the Senior Citizen fee waiver program. 11/17/1980